Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

1 Answer

a)

3x²-5x+m=0,

x=(5±√(25-12m))/6.

25-12m≥0 for non-complex roots.

Therefore 12m≤25, m≤25/12.

EXAMPLE

When m=0, x(3x-5)=0, x=0 or 5/3.

When m=2, x=(5±√(25-24))/6=(5±1)/6=1 or ⅔.

3x²-5x+2=(3x-2)(x-1).

So the solution is m≤25/12 (including, for example, m=0 and m=2).

b)

2(x²+mx)+6=m(x-1),

2x²+2mx-mx+6+m=0,

2x²+mx+6+m=0.

x=(-m±√(m²-8(6+m)))/4,

x=(-m±√(m²-8m-48))/4=(-m±√((m-12)(m+4)))/4.

When m=-4 or 12, the quadratic is a perfect square and has only one distinct root (x=1 when m=-4 and the quadratic is 2x²-4x+2=2(x-1)²; x=-3 when m=12 and the quadratic is 2x²+12x+18=2(x+3)²).

(m-12)(m+4)>0 when m>12 or m<-4.

So the solution to (b) is m>12 or m<-4 (for example, m=14 gives x=-2, -5 and the quadratic is 2x²+14x+20=2(x+2)(x+5); m=-6 gives the quadratic equation 2x²-6x=0=2x(x-3), x=0, 3).

by Top Rated User (815k points)

Related questions

1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
85,989 questions
91,894 answers
2,229 comments
23,906 users